CORRELATION OF ACTIVITIES WITH LEARNING OUTCOMES VOCATIONAL HIGH SCHOOL STUDENT - Muslim Chaniago (VANOS Journal of Mechanical Engineering Education, 2019)
This research is correlational with the aim of revealing the correlation between learning activeness with the final learning outcomes of Vocational High School students. The questionnaire is used to get data on student learning activeness distributed to students. Before the questionnaire is distributed, the questionnaire must be declared valid and reliable. While the learning outcomes data obtained from the report card grades. Analysis of research data using pearson product moment correlation. The correlation coefficient uses the t test formula. The results obtained r count = 0.4487 > r table = 0.279. While t count = 3.4785 > t table = 1.676 with a significant level used is 5%. The researcher can conclude that there is a positive and significant correlation between the learning activities of vocational high school students with their learning outcomes.